Bivalve mollusc culture research in Thailand (Department of Fisheries, 1988)
Comprehensive text covers all major aspects of the invertebrate class bivalve molluscs. Chapters cover morphology, ecology, feeding, reproduction, settlement and recruitment, growth, physiology, fisheries, aquaculture, genetics, diseases and parasites, and public health issues. Primarily for undergraduate students, but useful as a reference for postgraduate students and professionals.